Reason And Usage Of The Wise In Family Dispute Resolution Proceedings With The Implementation Of Judicial Decisions - MAHJOOB, S.; MAZAHERI KUHANSETANI, R.; TABATABAEI, M.S.; FASIHIZADEH, A. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT In recent years, the use of reason has been the subject of much attention by legal writers and prosecutors. The use of this argument in the family law system has led to many ambiguities to the extent that the doctrine and the judiciary have not been adequately addressed. Therefore, as an essential part of the legal system and the proper quality of citing it as a judicial proof by the prosecutors, it is of great importance that the present article discusses the position of this argument and its analysis. Judiciary is based on an Osule feghh. RESUMEN En los últimos años, el uso de la razón ha sido objeto de mucha atención por parte de escritores legales y fiscales. El uso de este argumento en el sistema de derecho de familia ha generado muchas ambigüedades en la medida en que la doctrina y el poder judicial no se han abordado adecuadamente. Por lo tanto, como parte esencial del sistema legal y la calidad adecuada de citarlo como prueba judicial por parte de los fiscales, es de gran importancia que el presente artículo discuta la posición de este argumento y su análisis. El poder judicial se basa en un Osule feghh.